Determination of the inductiveness of a physical model of track coils for high-speed transport - Holota, Oleksandr; Ustymenko, Dmytro; Mukha, Andriy; Plaksin, Serhiy; Chupryna, Yehor (Technology audit and production reserves, 2025)
The object of research is the parameters and characteristics of track coils with different design parameters for a physical model of high-speed maglev transport. The problem that arises in such a system is the untimely switching on of the track coils, which leads to a malfunction due to a short-term disappearance of the traction force. Solving this problem will allow the vehicle to improve the conditions of movement of the high-speed maglev transport. This will make it possible to make a reasonable choice of the parameters of the track coil of a physical model of high-speed transport, which would have the required inductance value at different switching modes. The required switching frequency will depend on the desired speed of movement of the vehicle and the parameters of the track coils. An important task within the framework of research on maglev transport is the development and creation of a fundamentally new control system. Such a system would have a track structure with traction coils of a rational shape and parameters that would implement certain control processes of the experimental unit. The task of the research is to create a physical model of track coils of high-speed transport and to conduct an experimental determination of the dependence of electrical parameters (inductance) on the frequency of a sinusoidal signal for different winding parameters of track coils. To implement the technical solution, a physical model of the track coil was created, which takes into account the necessary requirements for the study. The search for more favorable technological solutions requires conducting research on electrical processes in the track structure circuit of the physical model of the track coil. This will allow to substantiate the prerequisites for the creation, accumulation and transfer of the necessary energy to the track coils in physical models that will simulate the principles of movement and control of magnetic levitation transport. During the research, the results were obtained by applying mathematical statistics methods and the development of a track coil with optimal parameters for a physical model of a high-speed transport experimental unit was carried out. The results obtained with the correct selection of the track coil parameters can create prerequisites for the further development of an experimental switching system for physical model of high-speed transport. In this case, the operating reserve can be determined by the required reserve of effective operation of the track coils to implement the necessary laws of rolling stock control.